Efektivitas Aturan Hukum Penggunaan Masker Dalam Penanggulangan Kesehatan: Studi Pelaksanaan Peraturan Gubernur DKI Jakarta Nomor 3 Tahun 2021 tentang Peraturan Pelaksanaan Peraturan Daerah Nomor 2 Tahun 2020 tentang Penanggulangan Coronavirus Disease 2019 - Sigit Prayogo Soemodihardjo; Syahrul Adam; Indra Rahmatullah (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This study discusses the application of the use of masks in the Governor of DKI Jakarta Regulation No. 3 of 2021 concerning The Implementation Regulation of Regional Regulation No. 2 of 2020 on The Prevention of Coronavirus Disease 2019 whether it can run effectively through the realization of the application of health protocols in the handling of coronavirus in DKI Jakarta through the theoretical approach of effectiveness of legislation. This research is field research that describes and describes a situation by reviewing the results of data and interviews obtained through the relevant agencies and then describing and associating with applicable regulations to support research. The method used is qualitative by using the approach of legislation (statue approach). The results of this study showed an analysis of the Governor of DKI Jakarta Regulation No. 3 of 2021 concerning The Implementation Regulation of Local Regulation No. 2 of 2020 on The Prevention of Coronavirus Disease 2019 is associated with the theory of effectiveness of soerjono Soekanto law, so this regulation looks quite effective by looking at the legal factors itself, law enforcement factors, facilities or facilities that support in law enforcement , the societing factor itself, and the cultural factor.